Determinations of Labile Nutrients (Methylcobalamin, 5-Methyltetrahydrofolate, and Trans Menaquinone-7) in Oil- and Beadlet-Filled, Gastric-Resistant Capsule. (29th May 2020) - You, Hong; Yin, Yuhao; Ren, Kangzi; Liu, Zhiyan; Whaley, Jeffrey; Bucci, Luke; Alamdari, Nima; Wolf, Alicia
Abstract: Objectives: The dietary supplement industry has grown substantially, and advances in technology have played important roles in the development of new forms of dietary supplements and delivery systems. While it is recommended to use compendia methods for testing dietary supplements, the analytical methods in place are often developed for single ingredients or simple matrices and are not always fit to be used for solving modern matrix challenges. Oil- and beadlet-filled, gastric acid-resistant capsule (OBGRC) is designed to improve nutrient delivery and absorption. However, it is challenging to accurately analyze labile nutrients in OBGRCs because nutrients within different physical locations are difficult to separate, and lengthy sample preparations lead to nutrient degradation. We developed and validated analytical methods to determine methylcobalamin (MeB12), 5-methyltetrahydrofolate (5-MTHF), and trans menaquinone-7 (MK-7) in OBGRCs. Methods: MeB12 and 5-MTHF were extracted by completely dissolving the OBGRC shells using aqueous buffers and then applying hexane-facilitated liquid-liquid extraction to remove the oil phase and determined by RP-HPLC using superficially porous particles columns. For MK-7 analysis, the whole OBGRC was cut to open and the oil phase was collected to dissolve in a mixture of dimethyl sulfoxide/tetrahydrofuran/ethanol before analyzed by RP-HPLC with fluorescence detection after on-line, post-column zinc reduction. The methods were subjected to single-laboratory validations according to the United States Pharmacopeia (USP) guidelines for linearity, suitability, detection limits, specificity, accuracy, and precision. Results: The methods achieved chromatographic resolution of target analytes without the expensive requirement of ultra-high pressure liquid chromatography and/or mass spectrometry. The methods have wide analytical ranges (from at least 50% to 250% of the input concentrations), high precision (repeatability relative standard deviations ranging from 1.04% to 4.90%), and high accuracy (spike recovery rate ranging from 89.2% to 108%). Conclusions: All three methods passed USP method validation criteria and have the potential to be widely adopted to analyze MeB12, 5-MTHF, and MK-7 in similar matrices for quality control purposes. Funding Sources: The research funding was provided by Ritual and Eurofins.